Centering Ability and Canal Transportation of Three Reciprocal Files in Moderately Curved Canals - Indra Kanujaya; Wiena Widyastuti; Anastasia Elsa Prahasti; Johan Arief Budiman (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2025)
Assessing the complexity of the root canal’s curvature is one of the crucial factors for the root canal procedure to succeed. Iatrogenic complications can happen during the shaping procedure of the curved canal as it can deviate from the original anatomy, such as transportation and ledge. Therefore, maintaining the initial anatomy of the root canal’s curvature and its centering during instrumentation is essential during the shaping procedure. This ex vivo study aims to analyze the centering ability and canal transportation of three reciprocal file systems, with and without a glide path in moderately curved canals. Thirty-six root canals with moderate curvature from freshly extracted maxillary premolar with separated buccal and palatal root canals, first maxillary molar with separated mesiobuccal and distobuccal canals, and first mandibular molar with separated mesial canals were selected then distributed into six random groups (n=6) according to with and without glide path procedure (#15 K-file) before instrumentation with different reciprocal system (GP+WOG, GP+R, GP+RB, NGP+WOG, NGP+R, NGP+RB). The centering ability and transportation were evaluated by CBCT both before and after instrumentation. One-way Analysis of Variances was employed to analyze the data. (p<0.05).  There were significant differences in centering ability at the middle third (p<0.05) and transportation at the apical third and middle third (p<0.05). All techniques showed certain transportation, and none of them had perfect centering ability. Reciproc Blue had better canal centering and transportation compared to Reciproc when glide paths were used prior to instrumentation. All systems can shape the curved canal without iatrogenic complications.